NATURAL GAS POTENTIAL OF LAND FORMATION IN UKRAINE - Vytvitskyi, Y. S.; Lebega, O. V. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The analysis of the potential of natural gas resources of gas prospective shale formations in the main oil and gas basins of Ukraine, that is of Eastern, Western, Southern ones. On the basis of economic and mathematical modeling of geological and economic characteristics of shale formations, from which successful shale gas mining is currently being carried out in the world, correlation-regressive dependencies have been established. They allow to carry out a predicted estimation of the gas content, the initial rate of gas extraction wells, the marginal cost limit, at which a break-even production of natural gas from shale formations is possible. Using these dependencies, an analysis of the resource potential of slate formations has been carried out and it has been established that in the Eastern region stratigraphic complexes with promising shale formations are included: Devonian deposits - Upper Devonian (Famensian tier); coal deposits - Lower Carboniferous Complex (Tourney, Viseu, Serpukhov Tiers); middle-complex complex (Bashkir and Moscow tiers); Carboniferous complex (Kasimovsky and Gzhel tiers). Yevgenivsko-Druzhelyubivsk, Mirgorod-Livensk, Borkivsk-Velikzagorivsk and Zachipelsk-Livensk areas are the most investments-attractive in the prospects for shale gas extraction in the Eastern region. In the Western region, prospective stratigraphic complexes include deposits of the Cambrian, Silurian and Oligocene-Miocene age. The most investment attractive for shale gas extraction in the Western region is Davydivsky, Rava-Russkaya, East-Lishinskaya and Oleska districts. In the Southern region, perspective shale gas extraction is the deposits of the Middle Jurassic, the upper part of the Visean tier and the lower part of the Serpukhov tier of the carbon fiber of the Pre-Dobrug Trough. The results obtained can serve as a basis for investors to select priority objects for the development of natural gas resources from shale formations in Ukraine.